The establishment of a healthy lifestyle culture among students requires a combination of organizational and educational factors - Bobkov V.V.; Sviridov B.A.; Uvarova N.N.; Guruleva T.G. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to determine the organizational and educational factors that contribute to the development of a healthy lifestyle among young people, guided by their values. Methods and structure of the study. The research involved students from the first to fourth years of study at the Plekhanov Russian University of Economics, with a total of 441 participants, including both male and female students. The age range of the participants was between 17 and 25 years. In the initial phase, the participants were administered a survey using the M. Rokich «Value Orientations» method, which consisted of 18 questions. In the subsequent phase, the survey was conducted using an original questionnaire that focused on the participants’ behavior at school and at home, their current knowledge of human physiology, their understanding of healthy lifestyle principles, and their level of physical activity. Results and conclusions. The process of cultivating a healthy lifestyle culture requires a multifaceted approach. It should encompass interdisciplinary initiatives, imaginative tasks, and the integration of health-related themes into the social sciences and humanities. Additionally, it involves the dissemination of educational content through internal and external platforms, enhancing the curriculum with more engaging physical education classes, and addressing the needs of students by providing incentives for a healthy lifestyle. Furthermore, it is essential to conduct preventive medical examinations to raise awareness about one’s health status.